Family functioning and suicidal ideation in 5th year secondary school students in the district of San Juan de Miraflores - Pérez Carrillo, Paola Zenaida (2015)
Overall objective of this study was to determine the relationship between family functioning and suicidal ideation, in a sample of fifth year of secondary education in the District of San Juan de Miraflores. The sample was conformed by 104 students of both sexes of two educational institutions. Applied instruments were the scale for suicide ideation of Beck (ISB) and the scale of family functioning (family APGAR). Results revealed a significant relationship was found of (p < to 0.05), suicide ideation and family functioning, furthermore this relationship is inverse, so it is concluded that lower family functioning, increased suicidal ideation, and vice versa. Also adolescents in the sample have a medium level of suicidal ideation, and a severe level of family dysfunction, so we also found a significant relationship between the dimensions of attitude towards life and death, characteristics of the thoughts and desires suicide, suicidal intent and family functioning. The linear regression analysis dimensions, adaptation, affection and resources predict suicidal ideation, however significant values are not large-scale. With respect to family functioning and suicidal ideation exists prevalence of female on male.